(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Kazantseva L. I. Linguistic situation of the south-east region and taking into consideration it’s influence on to the process of education of preschool children of the Ukrainian language. Peculiarities of the linguistic situation of the south-east region of Ukraine are determined, the characteristics of the sociolinguistic environment as a factor of the formation of a preschool child’s personality are given.